Water treatment with new nanomaterials - Homaeigohar, Shahin (Water, 2020)
The studies introduced in this special issue aim to provide a state-of-the-art vision for nanomaterials-based technology that could profit the water treatment industry. Given the expanding crisis of water shortages across the world, this perspective is invaluable and of paramount importance. No doubt, as the environmental challenges are going to be more complicated and to extend to as-yet unconsidered areas, we need to upgrade our facilities and knowledge to address them properly. Nanomaterials are indeed promising building blocks for such advanced technologies that enable them to purify water streams from complex pollutants in an energy, cost and time-effective manner. The focus of the (review and original research) articles collected in this issue is on various kinds of nanomaterials made of carbon, polymer, metal, and metal oxides (magnetic and photocatalyst), that are employed for adsorption and photodegradation of heavy metals and organic pollutants, respectively. Here, I briefly review the insights given in these precious studies and suggest new directions for future research in this field.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Adsorption; Ecotoxicology; Membrane; Nanohybrids; Nanomaterial; Photocatalysis; Water treatment